2015
DOI: 10.1097/aog.0000000000000663
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chronic Pelvic Pain and Endometriosis With Signs of Sensitization and Myofascial Pain

Abstract: Objective To evaluate sensitization, myofascial trigger points, and quality of life in women with chronic pelvic pain with and without endometriosis. Methods A cross-sectional prospective study of women aged 18 to 50 with pain suggestive of endometriosis and healthy, pain-free volunteers without history of endometriosis. Patients underwent a physiatric neuro-musculoskeletal assessment of clinical signs of sensitization and myofascial trigger points in the abdominopelvic region. Pain symptoms, psychosocial, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(143 citation statements)
references
References 40 publications
7
130
0
6
Order By: Relevance
“…8 Clinical signs as a proxy for CS can be measured by a general, widespread lowering of pain thresholds, as observed in the present study. 9 Nonetheless, in accordance with Laursen et al, 13 our findings suggest that the reduced pain thresholds were not related to the presence of visible endometriosis lesions but to the state of persistent pain. In endometriosis, the ectopic lesions convey noxious signals that are also consolidated by the inflammatory factors activated around the lesions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…8 Clinical signs as a proxy for CS can be measured by a general, widespread lowering of pain thresholds, as observed in the present study. 9 Nonetheless, in accordance with Laursen et al, 13 our findings suggest that the reduced pain thresholds were not related to the presence of visible endometriosis lesions but to the state of persistent pain. In endometriosis, the ectopic lesions convey noxious signals that are also consolidated by the inflammatory factors activated around the lesions.…”
Section: Discussionsupporting
confidence: 90%
“…3 The pain often reduces quality of life (QoL) and is associated with reduced physical and mental well-being. 8 A few studies have indicated that women with endometriosis-associated pain might have widespread reduced pain thresholds and CS, [9][10][11][12][13] but more research on the subject is warranted to determine the pain mechanisms in order to optimize the treatment of the disease. CS is defined in animal models as dorsal horn neurons that give hyperactive responses to various sensory inputs.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established in the pain community (among both scientists and clinicians) that central changes occur in all chronic pain conditions and that the nervous system can both modulate pain or may itself be responsible for generating the sensation of pain. 78 There is good evidence that these changes also occur in conditions associated with pelvic pain [79][80][81] including endometriosis. 82,83 However, in the majority, these studies are descriptive, providing no information on cause and effect nor relating central changes to potential pain generators in the periphery.…”
Section: Painmentioning
confidence: 99%
“…These results together establish that the inflammatory response of endometriosis lesions initiates a cascade of events resulting in enhancement of the responsiveness of nociceptors and DRG neurons, and inhibition of EP2/EP4 suppresses these pain pathways and decreases endometriosis-induced pelvic pain. In women with endometriosis, the pelvic pain can be assessed by bilateral hyperalgesia and allodynia from T9-S1 spinal segments (25) and mechanical hyperalgesia of the pelvis, where pain is reported in response to applied pressure. Although the von-Frey DRG mice models are widely used to measure hyperalgesia in pain models, we used this interactive approach, to our knowledge for the first time, to measure the pelvic floor pain threshold in endometriosis chimeric mouse model with translational relevance.…”
Section: Inhibition Of Ep2/ep4 Decreased Angiogenesis Of Endometriosimentioning
confidence: 99%